CULTURAL STIGMA AGAINTS TAMIL WOMEN IN INDIA - Khaula Abubakar; Saprudin (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
This study aims to analyze the cultural stigma experienced by Tamil women in the film Pad Man. This film depicts the struggle of a man and husband of a woman from the Tamil tribe who still believes in the customs there, where the man tries to change people's views on menstruation and sanitary napkins. This research uses a descriptive qualitative method with a content analysis approach to identify the cultural stigma that appears in the movie Pad Man.